STUDY ON THE IMPACT OF LACK OF NUTRIENTS ON HEALTH OF ADOLESCENT GIRLS IN THE CHANGING ENVIRONMENT - Sinha, Anita; Chandra, Anjali; Kumari, Kusum; Mishra, Vidisha; Priyadarshini, Shweta; Rani, Sangeeta; Renu Kumari (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Nutrition is a basic need of human life. The fastest growth and development in human life occurs during adolescence. This stage usually lasts from 13 to 19 years. During this period, many types of changes occur in adolescent girls along with physical growth. Nutrition is a combination of those processes by which any living being obtains food items and uses nutrients to perform physical functions, for growth and for the reconstruction of its components. Nutrition refers to that powerful process in which the food taken is used to provide nutrition to the body. Many types of problems arise due to lack of nutrition in adolescence. In this study, by taking information about the food items taken by adolescent girls daily, the demand of nutrients present in them has been assessed. The health of adolescent girls has been assessed by studying the deficiency of nutrients in daily diet and its ill effects.